RELATIONSHIP OF GROWTH AND YIELD MINI TUBERS OF POTATO UNDER COCOPEAT MEDIA AND FREQUENCY OF FERTILIZER - Fajrin Pramana Putra; Saparso Saparso; Slamet Rohadi Suparto; Khavid Faozi (Bernas : Jurnal Penelitian Pertanian, 2019)
The research aimed to determine the growth variable correlated to the mini tubers yield of potato and obtained the media thickness of cocopeat and frequency of fertilizer which was good for growth and yield of potato mini tubers. The research is arranged to use complete randomized block design with three replications. The main factor was the thickness of media cocopeat with three levels, which was 10 cm, 15 cm and 20 cm. The second factor was the frequency of nutrients with two levels, which was three days and six days. The results of the research showed that the number of mini tubers yield were influenced by frequency of fertilizer and were not the thickness of cocopeat media.The number of mini tubers yield were correlated with height plant, leaf area, root length, number of stolon, and stolon effectivity. The number mini tubers yield were most affected by number of stolon, and stolon effectivity with the regression model that was Ŷ = - 4.21588** – 0.00338 XPHns + 0.00003 XLAns – 0.00377 XRLns + 0.52317 XNST** + 0.08233 XSE**.